A case study driven integrated methodology to support sustainable urban regeneration planning and management - Jesus, Eduardo Natividade (2019)
Urban regeneration involves the integrated redevelopment of urban deprived areas, covering physical, socio-economic and environmental aspects of cities, and it is concerned with interventions on early/inner-ring suburbs and historic centers, which are under pressure from population growth and sustainable development policies. The planning and management of urban regeneration interventions usually depend on the city and regional context. Although these interventions involve multiple issues and stakeholders, common characteristics can be identified, thus appealing for a holistic vision and coordination among the various dimensions of the problem. Based on the above context, and on the experience from a large-scale urban regeneration project, this article introduces an integrated methodology to support the planning and management of urban regeneration interventions. The methodology proposes a flexible baseline that can be adapted to urban regeneration projects of different contexts and dimensions, and defines steps, the corresponding stakeholders, and the teams’ engagement, in an integrated framework to plan and oversee urban regeneration actions towards more sustainable and resilient interventions.